Using animation-based instructional media in probability lesson - Arfita Ade Nur Insani; Maria Ulpah; Wan Alawee Samaeng (Universitas Sarjanawiyata Tamansiswa, 2025)
Probability is one of the most conceptually challenging topics in secondary mathematics, particularly for students who struggle to visualize sample spaces, interpret random events, and distinguish between theoretical and empirical probability. This study aims to explore how animation-based instructional media support students’ conceptual understanding of probability. Using a qualitative descriptive approach embedded within a research and development framework, data were collected through classroom observations, teacher interviews, and open-ended student responses at MTs Negeri 2 Brebes. The findings demonstrate that animated videos reduce cognitive load by providing step-by-step visualizations, narration, and sequential cues that clarify abstract concepts. Instructionally, the media was embedded within the lesson sequence, introduced briefly before instruction, played during concept explanation, and revisited as reinforcement during follow-up exercises. Students reported improved comprehension, stronger retention, and greater confidence when solving probability problems. The media also enhanced participation, with students asking more questions and engaging actively in discussions. Moreover, the animations helped correct common misconceptions by modeling accurate and inaccurate reasoning patterns. The study demonstrates that animation-based media can transform the learning experience by supporting affective engagement, and enabling more coherent mental models of probability. These results highlight the pedagogical potential of integrating dynamic visualizations into mathematics instruction and provide a foundation for future development of multimedia learning tools. This study contributes to mathematics education by demonstrating how animation functions as an instructional scaffold embedded within lesson sequencing to support students’ conceptual understanding of probability, providing process-oriented qualitative evidence of how dynamic visualizations shape reasoning, representation shifts, and misconception repair in classroom instruction.